Immune Privilege of Heart Valves - Hill, Morgan Ashley; Kwon, Jennie H.; Gerry, Brielle; Hardy, William A.; Walkowiak, Olivia Agata; Kavarana, Minoo N.; Nadig, Satish N.; Rajab, T. Konrad (Frontiers in Immunology, 2021)
Immune privilege is an evolutionary adaptation that protects vital tissues with limited regenerative capacity from collateral damage by the immune response. This concept was first proposed by Sir Peter Medawar, who identified the anterior chamber of the eye and the brain as classical examples. More recently, the placenta, testes and articular cartilage were found to have similar immune privilege. What all of these tissues have in common is their vital function for evolutionary fitness and a limited regenerative capacity. Immune privilege is clinically relevant, because corneal transplantation and meniscal transplantation do not require immunosuppression. The heart valves also serve a vital function and have limited regenerative capacity after damage. Moreover, experimental and clinical evidence from heart valve transplantation suggests that the heart valves are spared from alloimmune injury. Here we review this evidence and propose the concept of heart valves as immune privileged sites. This concept has important clinical implications for heart valve transplantation.